Smoking Prevalence Increases following Canterbury Earthquakes - Nick Erskine; Vivien Daley; Sue Stevenson; Bronwen Rhodes; Lutz Beckert (The Scientific World Journal)
Background. A magnitude 7.1 earthquake hit Canterbury in September 2010. This earthquake and associated aftershocks took the lives of 185 people and drastically changed residents’ living, working, and social conditions. Aim. To explore the impact of the earthquakes on smoking status and levels of tobacco consumption in the residents of Christchurch. Methods. Semistructured interviews were carried out in two city malls and the central bus exchange 15 months after the first earthquake. A total of 1001 people were interviewed. Results. In August 2010, prior to any earthquake, 409 (41%) participants had never smoked, 273 (27%) were currently smoking, and 316 (32%) were ex-smokers. Since the September 2010 earthquake, 76 (24%) of the 316 ex-smokers had smoked at least one cigarette and 29 (38.2%) had smoked more than 100 cigarettes. Of the 273 participants who were current smokers in August 2010, 93 (34.1%) had increased consumption following the earthquake, 94 (34.4%) had not changed, and 86 (31.5%) had decreased their consumption. 53 (57%) of the 93 people whose consumption increased reported that the earthquake and subsequent lifestyle changes as a reason to increase smoking. Conclusion. 24% of ex-smokers resumed smoking following the earthquake, resulting in increased smoking prevalence. Tobacco consumption levels increased in around one-third of current smokers.